Total Intravenous Anesthesia and Target Controlled Infusions : A Comprehensive Global Anthology - Absalom, Anthony R.; Mason, Keira P. (Springer International Publishing : Imprint: Springer, 2017)
This is a comprehensive and authoritative presentation of total intravenous anesthesia (TIVA) and target controlled infusion (TCI). The editors' international reputation has enabled them to recruit leading experts from around the world to write single-author chapters in their area of expertise. Total Intravenous Anesthesia and Target Controlled Infusions is the first multi-disciplinary, globally authored volume on the topic. Providing a single source of information on all aspects of TIVA and TCI, from pharmacologic modeling and the pharmacology of intravenous anesthetic drugs to practical considerations in the clinical setting and the requirements of special populations, Total Intravenous Anesthesia and Target Controlled Infusions examines the debate about the risks and advantages of TIVA, analyze outcome studies, and provides guidance on creating a curriculum to teach TIVA and TCI.
Keywords: Medicine.; Anesthesiology.; Traumatology.; elektronické knihy; electronic books